Do military expenditure and conflict affect economic growth in Sri Lanka? evidence from ARDL bound test approach - A.R, Sithy Jesmy; Abd Karim, Mohd Zaini; Applanaidu, Shri Dewi (2015)
Conflict in the form of civil war, ethnic tensions and political conflict is an on-going concern in the developing world as well major bottleneck to the economic development in Sri Lanka.Three decades of civil war and unethical political culture pushed the country to severe economic problems, slower rate of economic growth and heightened defense budget.The aim of this study is to examine the effect of military expenditure and conflict on economic growth in Sri Lanka between 1976 and 2013 using the Solow growth model and ARDL bound test approach.The results of bound test are highly significant and leading to co integration.The coefficients of the error correction terms are negative and highly significant.The estimated empirical results show that, the coefficient of military expenditure is negative and highly significant in the short-run as well as in the long-run to determine GDP per capita growth rate.Moreover, the coefficient of military participation shows negative in the long-run as well as in the short run but not statistically significant.In addition, dummy variable represented for conflict is negative and statistically significant to determine GDP per capita growth in Sri Lanka in the short-run as well as in the long-run.The results of this study clearly show that conflict and related military budget, decrease per capita GDP growth in Sri Lanka.Hence, it is critically important to take necessary action to decrease military budget and provide an efficient political solution to the minority problem at least in this post war scenario.It is also important to allocate efficient and optimum resources to all the sectors in the economy.